Determinants of capital structure change in terms of coefficients and significance during the 2008 financial crisis period An empirical study on UK companies - Rong, Xiyu (2012)
Capital structure decision is a research area that has been explored by many scholars. There are plenty theories and empirical studies trying to interpret the factors that influence leverage ratio of a firm. To further examine the capital structure determinants change in the period of 2008 financial crisis of the UK listed companies, I used two periods’ data to regress the same model and compare their coefficients and significances via STATA. The independent variables include corporate tax, size, investment opportunity, profitability, liquidity and tangible asset ratio. This dissertation aims at comparing the determinants of capital structure before and during the 2008 financial crisis of UK listed companies using secondary firm-level panel data. The research results reflect the change in the coefficients of firm-specific factors under the financial recession’s influence. The main contribution of this dissertation is the estimation of determinants of capital structure and compares the differences in estimated coefficients of the two periods’ regression thus gives a suggested model for corporate to estimate the capital structure for the company and its competitors in different scenarios.